Black Muslim Theology and the Classical Islamic Tradition - Wesley Williams (International Institute of Islamic Thought, 2008)
Elijah Muhammad declared unapologetically that “God is aman.” This anthropomorphist doctrine does violence to modern normative Islamic articulations of tawú¥d (monotheism), the articulations of which involve God’s “otherness” from the created world. The Nation of Islam (NOI), therefore, has been the target of polemics from Muslim leaders who, from within and without the United States, have declared its irredeemable heterodoxy. But in premodern Islam, heresy was in the eye of the beholder and “orthodoxy” was a precarious and shifting paradigm. This paper attempts to, in the words of Zafar Ishaq Ansari, “examine how the ‘Nation of Islam’ fits into the framework of Islamic heresiology.”